Towed target positioning technology based on long baseline and ultra-short baseline combination - Wu Jingbo; Cheng Shuping; Zhao Pengduo (Zhongguo Jianchuan Yanjiu, 2019)
[Objectives] This research aims to obtain accurate positioning in underwater towing and facilitate its use and deployment during experiments.[Methods] Long baseline and ultra-short baseline acoustic technology are combined,the rough position of a towed target is obtained using the ultra-short baseline positioning array and the position is used as a priori data for long baseline positioning. On this basis,the long baseline array elements of the deck unit transducer and ultra-short baseline positioning array are combined with the short-term baseline positioning a priori data and long baseline positioning technology so as to obtain higher positioning accuracy.[Results] The long-baseline and ultra-short baseline joint positioning method is used to improve the positioning accuracy of towed underwater targets. The results of positioning accuracy tests conducted on a lake show that the Root-Mean-Square(RMS) error is 6.8 m when the ultra-short baseline method is adopted. However,the RMS value is just 2.5 m when the long baseline and ultra-short baseline are combined,solving the problem of positioning accuracy within short distances.[Conclusions] By combining the long-range baseline information of the deck unit's ranging information and the ultra-short baseline positioning results,this technology can achieve the high-precision positioning of towed underwater targets and provide technical support for the specific needs of offshore testing and operations.